2011
DOI: 10.1038/ncomms1426
|View full text |Cite
|
Sign up to set email alerts
|

Local BMP receptor activation at adherens junctions in the Drosophila germline stem cell niche

Abstract: According to the stem cell niche synapse hypothesis postulated for the mammalian haematopoietic system, spatial specificity of niche signals is maximized by subcellularly restricting signalling to cadherin-based adherens junctions between individual niche and stem cells. However, such a synapse has never been observed directly, in part, because tools to detect active growth factor receptors with subcellular resolution were not available. Here we describe a novel fluorescence-based reporter that directly visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
100
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(112 citation statements)
references
References 59 publications
4
100
1
Order By: Relevance
“…In the ventricular region of the developing brain N-cadherin is required for maintaining NSCs by preventing differentiation via regulation of Akt signaling (Zhang et al, 2010). Finally, in the Drosophila testis, BMP receptor complexes are localized to Ecadherin-rich AJs at the stem cell-niche junction, which might help restrict BMP signaling activity to the GSC niche (Michel et al, 2011). These lines of evidence support a role for cadherins in the regulation of cell signaling pathways important for stem cell selfrenewal and proliferation (Fig.…”
Section: Controlling Stem Cell Self-renewal Via Signalingmentioning
confidence: 74%
“…In the ventricular region of the developing brain N-cadherin is required for maintaining NSCs by preventing differentiation via regulation of Akt signaling (Zhang et al, 2010). Finally, in the Drosophila testis, BMP receptor complexes are localized to Ecadherin-rich AJs at the stem cell-niche junction, which might help restrict BMP signaling activity to the GSC niche (Michel et al, 2011). These lines of evidence support a role for cadherins in the regulation of cell signaling pathways important for stem cell selfrenewal and proliferation (Fig.…”
Section: Controlling Stem Cell Self-renewal Via Signalingmentioning
confidence: 74%
“…BMP signaling complexes are thought to function in this manner in the maintenance of stemness (Michel et al, 2011) and in epithelial-tomesenchymal transition (Zeisberg et al, 2003).…”
Section: Possible Functions For Synaptic Pmadmentioning
confidence: 99%
“…In addition, BMP-Smad1 signaling controls many other aspects of development and tissue homeostasis and its dysregulation leads to the development of a number of diseases, including cancer and skeletal and vascular diseases. In addition, BMPs are present in the bloodstream and in the microenvironments of many adult stem cells, including neural stem cells, mesenchymal stem cells and skin stem cells [7,11,13]. Therefore, it is reasonable to predict that many cells encounter BMPs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that BMPs can stimulate cell proliferation under certain conditions [13,42]. Previous studies have also established that SXS phosphorylation is essential for Smad1 function.…”
Section: Serum Starvation Altered the Dynamics And Amplitude Of Bmp-smentioning
confidence: 99%
See 1 more Smart Citation